Membrane-bound ribosomes of myeloma cells. II. Kinetic studies on the entry of newly made ribosomal subunits into the free and the membrane- bound ribosomal particles (The Rockefeller University Press, 1975)
The kinetics of appearance of newly made 60S and 40S ribosomal subunits in the free and membrane-bound ribosomal particles of P3K cells were explored by determining the specific radioactivities of their 18S and 28S RNA after various lengths of [3H]uridine pulse. Both 40S and 60S subunits enter free and membrane-bound polyribosomes at comparable rates from the cytoplasmic pool of newly made, free native subunits, the 40S subunits entering the native subunit pool and the polyribosomes slightly earlier than the 60S subunits. At all times, the specific radioactivity of the membrane-bound native 60S subunits was slightly lower than that of the polyribosomal 60S subunits. This indicates that the membrane-bound native 60S subunits are not precursors destined to enter membrane-bound polyribosomes and suggests that they result from the dissociation of ribosomes after chain termination. The results observed also suggest that the membrane-bound native 60S subunits are not reutilized before their release from the membranes, which probably takes place shortly after dissociation from their 40S subunits. The monoribosomes, both free and membrane-bound, had the lowest specific radioactivities in their subunits. Finally, a small amount of newly made native 40S subunits, containing 18S RNA of high specific radioactivity, and apparently also newly made messenger RNA were detected on the membranes. The high turnover of these membrane-bound native 40S subunits suggests that they may represent initiation complexes formed with mRNA which has just reached the membranes and which has not yet given rise to polyribosomes.